Integration of Six Sigma Methodology to Reduce Complications in a Private Hemodialysis Center - Ekinci, Celil Gokay; Taner, Mehmet Tolga; Erbas, Engin (International Review of Management and Marketing, 2015)
This paper aims to evaluate the complications occurred during and after the hemodialysis sessions made in a private hemodialysis center in terms of their sigma levels and severity. Complications with sigma levels under 4.00 sigma level indicate that the sessions need improvement and corrective actions. Vital few and trivial many critical to quality (CTQ) factors are determined and some improvement suggestions are made for the process based on the vital few CTQ factors. Keywords: Six Sigma; Haemodialysis; Complications JEL Classifications: I20; L15